Cell-Penetrating Penta-Peptides (CPP5s): Measurement of Cell Entry and Protein-Transduction Activity - Masaru Miyagi; Shigemi Matsuyama; Justine Ngo; Dagmar Hajkova; I-Ju Yeh; Vivian Gama; Jose A. Gomez; Joseph Chen (MDPI AG, 2010)
Previously, we developed cell-penetrating penta-peptides (CPP5s). In the present study, VPTLK and KLPVM, two representative CPP5s, were used to characterize the cell-penetration and protein-transduction activities of these small molecules. Various inhibitors of endocytosis and pinocytosis (chlorpromazine, cytochalasin D, Filipin III, amiloride, methyl-b-cyclodextrin, and nocodazole) were tested. Only cytochalasin D showed suppression of CPP5 entry, though the effect was partial. In addition, CPP5s were able to enter a proteoglycan-deficient CHO cell line. These results suggest that pinocytosis and endocytosis may play only a minor role in the cell entry of CPP5s. By mass spectrometry, we determined that the intracellular concentration of VPTLK ranged from 20 nM to 6.0 mM when the cells were cultured in medium containing 1 mM - 1.6 mM VPTLK. To determine the protein-transduction activity of CPP5s, the Tex-LoxP EG cell line, which has a Cre-inducible green fluorescent protein (GFP) gene, was used. VPTLK and KLPVM were added to the N-terminus of Cre, and these fusion proteins were added to the culture medium of Tex-LoxP EG cells. Both VPTLK-Cre and KLPVM-Cre were able to turn on GFP expression in these cells, suggesting that CPP5s have protein-transduction activity. Since CPP5s have very low cytotoxic activity, even at a concentration of 1.6 mM in the medium, CPP5s could be utilized as a new tool for drug delivery into cells.